From Microscopy to Nanoscopy: Defining an Arabidopsis thaliana Meiotic Atlas at the Nanometer Scale - Sims, Jason; Schlögelhofer, Peter; Kurzbauer, Marie-Therese (Frontiers in Plant Science, 2021)
Visualization of meiotic chromosomes and the proteins involved in meiotic recombination have become essential to study meiosis in many systems including the model plant Arabidopsis thaliana. Recent advances in super-resolution technologies changed how microscopic images are acquired and analyzed. New technologies enable observation of cells and nuclei at a nanometer scale and hold great promise to the field since they allow observing complex meiotic molecular processes with unprecedented detail. Here we provide an overview of classical and advanced sample preparation and microscopy techniques with an updated Arabidopsis meiotic atlas based on super-resolution microscopy. We review different techniques, focusing on STED nanoscopy, to offer researchers guidance for selecting the optimal protocol and equipment to address their scientific question.